Study of reactivity of cyanoacetohydrazonoethyl-N-ethyl-N-methyl benzenesulfonamide: preparation of novel anticancer and antimicrobial active heterocyclic benzenesulfonamide derivatives and their molecular docking against dihydrofolate reductase. (4th November 2016) - Debbabi, Khaled F.; Al-Harbi, Sami A.; Al-Saidi, Hamed M.; Aljuhani, Enas H.; Abd El-Gilil, Shimaa M.; Bashandy, Mahmoud S.
Abstract: This article describes the synthesis of some novel heterocyclic sulfonamides having biologically active thiophene3, 4, 5, 6, coumarin8, benzocoumarin9, thiazole7, piperidine10, pyrrolidine11, pyrazole14 and pyridine12, 13 . Starting with 4-(1-(2-(2-cyanoacetyl)hydrazono)ethyl)-N-ethyl-N-methylbenzenesulfonamide(2), which was prepared from condensation of acetophenone derivative1 with 2-cyanoacetohydrazide. The structures of the newly synthesized compounds were confirmed by elemental analysis, IR, 1 H NMR, 13 C NMR, 19 F NMR and MS spectral data. All the newly synthesized heterocyclic sulfonamides were evaluated as in-vitro anti-breast cancer cell line (MCF7) and as in-vitro antimicrobial agents. Compounds8, 5 and11 were more active than MTX reference drug and compounds12, 7, 4, 14, 5 and8 were highly potent against Klebsiella pneumonia . Molecular operating environment performed virtual screening using molecular docking studies of the synthesized compounds. The results indicated that some prepared compounds are suitable inhibitor against dihydrofolate reductase (DHFR) enzyme (PDBSD:4DFR) with further modification.